THE EFFECT OF BRAND IMAGE, PRODUCT QUALITY, PROMOTION, AND INFLUENCER MARKETING ON ONLINE PURCHASE INTENTION FOR STREETWEAR FASHION PRODUCTS: CASE STUDY OF IT’S B APPAREL - Fauzan, Naufal Hilmy; Bernardus, Denny (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
Streetwear fashion business has become one of the most dynamic sectors and has the potential to generate large profits, especially in online sales. With the existing potential, it becomes a positive opportunity in the It’s B Apparel business which is engaged in the streetwear fashion business. This study aims to determine the effect of brand image, product quality, promotion, and influencer marketing on online buying interest. The study used a quantitative approach with 200 respondents and the data was processed using the SmartPLS tool. The results showed that brand image had a negative and significant effect on online buying interest with a T-Statistic value of 5.689 and a correlation of 0.765 , product quality had a positive and significant effect on online buying interest with a T-Statistic value of 3.741 and a correlation of 0.851, promotion had a positive and significant effect on online buying interest with a T-Statistic value of 8.039 and a correlation of 0.898 , and promotion had a positive and significant effect on online buying interest moderated by influencer marketing with a T-Statistic value of 2.196 and a correlation of 0.483. The implications are in improving product quality, product innovation, social media marketing and loyalty programs.